Industrialized childbirth, birth in the 21st century, and dialogues with psychology - Beatriz Guedes Mattoso; Cláudia Helena Cerqueira Mármora; Sara Ribeiro Carvalho; Tays Aparecida da Silva; Thamiris Ribeiro (Estudos de Psicologia (Campinas))
Abstract Objective The present article aims to investigate how female bodies and subjectivities are understood at the moment of childbirth, considering historical, social, and political contexts. It also intends to reflect on the subject, weaving a dialogue with Psychology from there. Method It consists of a critical review of literature from different bibliographic sources, exploring classic texts and newspaper articles. Results It is considered that human birth is influenced by different factors, including biomedical, market-driven, and neoliberal logics. At this point, the commitment of this scientific discipline is highlighted, as well as its role in producing knowledge and ensuring women’s rights over their bodies. Conclusion The authors believe that Psychology should be linked to the production of ethical and critical knowledge that seeks change and new horizons, distancing itself from the current project that marginalizes the demands of minorities, including women.